Filipinx American studies reckoning, reclamation, transformation - Bonus, Rick 1962-; Tiongson, Antonio T., Jr. 1968-
This volume spotlights the unique suitability and situatedness of Filipinx American studies both as a site for reckoning with the work of historicizing U.S. empire in all of its entanglements, as well as a location for reclaiming and theorizing the interlocking histories and contemporary trajectories of global capitalism, racism, sexism, and heteronormativity. It encompasses an interrogation of the foundational status of empire in the interdiscipline; modes of labor analysis and other forms of knowledge production; meaning-making in relation to language, identities, time, and space; the critical contours of Filipinx American schooling and political activism; the indispensability of relational thinking in Filipinx American studies; and the disruptive possibilities of Filipinx American formations. A catalogue of key resources and a selected list of scholarship are also provided.